The Darfur Refugees' Plight - Anna Praz (Graduate Institute Publications, 2014)
The Darfur crisis has left behind a profound legacy of displacement, with some 300,000 refugees camped on the Chadian side of the border and about 2 million displaced internally within Darfur. Despite a reduction in armed hostilities and violent casualties since 2006, as well as a peace agreement signed at Doha in 2011, limited signs of voluntary repatriation are visible from eastern Chad; where refugees are seemingly willing, but not ready, to return. Further to the Doha peace settlement, th...